Photodynamic therapy in oral potentially malignant disorders—Critical literature review of existing protocols - Figueira, Jéssica Araújo [UNESP]; Veltrini, Vanessa Cristina (Elsevier, 2017)
Introduction Oral cancer is a serious public health issue. Apart from its high rate of prevalence, incidence and mortality, it can often result in more complex and expensive treatment when diagnosed late. Potentially malignant disorders (PMDs) can precede oral cancer, and are usually treated by surgical excision. However, in many cases patients are elderly and multiple interventions may be required. Photodynamic therapy (PDT) is a simple alternative, which has been successfully used in the treatment of oral PMDs. Objective Due to the lack of standardization regarding photosensitizers (PTSs), types of irradiation, and methods of application, the objective of this study was to analyze existing PDT protocols in an attempt to identify the one that demonstrates greater efficiency, reliability and feasibility in the treatment of oral PMDs for both researchers and clinicians. Methods Original clinical studies published only in English between 1993 and 2016 were searched in Pubmed/Medline database using the following keywords: photodynamic therapy; oral potentially malignant disorder; oral premalignant lesions. Review articles; experimental studies; case-reports; commentaries; and letters to the Editor were excluded from the selection. Results and conclusion Based on the 16 studies selected, the topical 5-ALA-20% PTS, associated to a LED light applied for 15 min with a 7-day interval between sessions emerged as the most frequently used PDT protocol, with satisfactory results. Due to its low rate of side effects, this PDT protocol presents good potential for the treatment of oral PMDs. Further clinical studies are required to ascertain its long-term validity in preventing oral cancer.
Keywords: Clinical protocols; Oral cancer; Oral dysplasia; Oral medicine; Oral potentially malignant disorders; Oral premalignant lesions; Photodynamic therapy